The effects of treatment with Mebendazole on gizzard worm infections in captive Swan Geese Anser cygnoides - Bailey, T A; Brown, J J; Avery, R A (Wildfowl, 1990)
Eggs of the gizzard worm Amidostomum anseris in faeces of a flock of captive Swan Geese in the Tower Pen at Slimbridge were monitored over three months, which included a period of routine worming with the anthelmintic drug Mebendazole. Parasite eggs disappeared from the faeces of all the treated birds which were examined, but reinfection occurred rapidly, eggs reappearing in the faeces between 15 and 28 days of the cessation of worming. It is estimated that prior to worming, the flock was contaminating the Tower Pen with slightly more than 200,000 parasite eggs per day.